Toxicokinetic Model Development for the Insensitive Munitions Component 2, 4-Dinitroanisole. (September 2015) - Sweeney, Lisa M.; Goodwin, Michelle R.; Hulgan, Angela D.; Gut, Chester P.; Bannon, Desmond I.
The Armed Forces are developing new explosives that are less susceptible to unintentional detonation (insensitive munitions [IMX]). 2, 4-Dinitroanisole (DNAN) is a component of IMX. Toxicokinetic data for DNAN are required to support interpretation of toxicology studies and refinement of dose estimates for human risk assessment. Male Sprague-Dawley rats were dosed by gavage (5, 20, or 80 mg DNAN/kg), and blood and tissue samples were analyzed to determine the levels of DNAN and its metabolite 2, 4-dinitrophenol (DNP). These data and data from the literature were used to develop preliminary physiologically based pharmacokinetic (PBPK) models. The model simulations indicated saturable metabolism of DNAN in rats at higher tested doses. The PBPK model was extrapolated to estimate the toxicokinetics of DNAN and DNP in humans, allowing the estimation of human-equivalent no-effect levels of DNAN exposure from no-observed adverse effect levels determined in laboratory animals, which may guide the selection of exposure limits for DNAN.